Invisible labour: the role of institutionalised xenophobia in shaping the experiences of migrant domestic workers in South Africa - Fuma, Melany (Department of Sociology, 2025)
Xenophobia remains a persistent issue in South Africa, shaping the country's transition from apartheid to democracy and continuing to marginalise migrant workers, particularly in the domestic labour sector. Migrant domestic workers, many of whom come from neighbouring African countries, face systemic exclusion, precarious employment conditions, and, in some cases, outright violence. This dissertation investigates how institutionalised xenophobia has contributed to the exploitation and marginalisation of migrant domestic workers in both apartheid and post-apartheid South Africa. Existing scholarship on xenophobia in South Africa highlights its historical roots in colonial and apartheid-era policies, which entrenched racialised labour hierarchies and exclusionary nationalism. While much of the literature focuses on contemporary xenophobic violence, fewer studies trace the historical continuities between apartheid-era discrimination and present-day exclusionary labour practices. This study builds on works examining the intersections of race, gender, and migration in South Africa's labour market, contributing to the discourse by situating migrant domestic workers within this broader historical trajectory. This dissertation seeks to answer the question: How has institutionalised xenophobia, across both the apartheid and post-apartheid eras, shaped the marginalisation and exploitation of migrant domestic workers in South Africa? Using a comparative analysis of scholarly literature and historical policy documents, it examines the persistence of exclusionary labour practices and social attitudes toward migrant domestic workers. The findings reveal that xenophobia in South Africa is not merely an expression of individual prejudice but a systemic issue embedded in historical labour structures and nationalist ideologies. While the transition to democracy introduced legal protections for workers, migrant domestic workers continue to experience discrimination, social exclusion, and economic precarity. The study concludes that contemporary xenophobia is deeply rooted in the racialised labour regimes of apartheid and remains a structural force shaping the experiences of migrant domestic workers today. By tracing these historical continuities, this dissertation contributes to debates on migration, labour, and social justice, offering insights into the policies and interventions needed to create a more inclusive and equitable society.